Realistic Determination of Live Loads on Various Reinforced Concrete Structures - Soomro, Z.; Khoso, S.; Ali, T.; Abbasi, S. A.; Ansari, A. A.; Naqash, M. T. (Engineering, Technology & Applied Science Research, 2022)
This paper presents various case studies of examined and calculated live loads on reinforced concrete structures. These case studies accumulated information and data of existing structures about their design live loads and acquired detailed drawings showing the reinforcement in their floor slab sections. The actual occupancy loads that act on the floor slabs were assessed, and the ultimate loads that an individual slab section should be able to support were calculated using the methods recommended by ACI, CP-114, CP-110, and the yield line theory. A reinforced concrete slab panel was also tested to check the validity of the theoretically predicted ultimate loads. The results were compared to find a safety margin and, if necessary, recommend lower live load outlines for cost reduction. The case studies showed that there is sufficient margin to reduce design live loads on the floor slabs of residential buildings, especially in multistory apartment blocks. Moreover, it was found that the live loads, especially on residential buildings, could be decreased to two-thirds of the code values without risking floor overloading.